Benign Rapidly Growing Ovarian Dermoid Cysts: A Case Series. (January 2017) - Deguchy, Qurieno; Fananapazir, Ghaneh; Corwin, Michael; Lamba, Ramit; Gerscovich, Eugenio; McGahan, John
Dermoid cysts are thought to be slow-growing tumors. This case series provides 2 clinical examples of sizeable growth of benign ovarian dermoid cysts in premenopausal patients. These patient cases were imaged initially; however, adnexal masses were not present on computed tomography images of the pelvis. Follow-up examination with sonography did demonstrate the presence of sizeable adnexal masses, which were confirmed by histology to represent benign dermoid cysts. Therefore, it may be wise to still consider ovarian dermoid cyst in the differential diagnosis in the setting of an adnexal mass that demonstrates the sonographic characteristics of a dermoid, even when absent on prior recent examinations.